Pengaruh Kompetensi dan Kompensasi Melalui Motivasi Serta Dampaknya terhadap Kinerja Aparatur Sipil Negara pada Kementrian Agama Kabupaten Muaro Jambi - Syamsir, Syamsir; Syeikh, Saiyid; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to describe the competence, compensation, motivation and performance of ASN of the Ministry of Religion of Muaro Jambi Regency and to analyze the partial and simultaneous direct and indirect influence of competence and compensation on ASN motivation and performance, as well as to analyze motivation on ASN performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely competence, compensation, motivation and performance. Apart from that, the author also looks for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this research is employees of the Ministry of Religion, Muaro Jambi Regency, totaling 76 employees with conditions in 2022. The data analysis technique used in this research is through path analysis followed by hypothesis testing via F (simultaneous) and t (partial) tests. From the path analysis tests carried out, it was found that competence and compensation have an influence on ASN motivation and performance, both directly and indirectly. This explains that if the organization has high competence and higher compensation, this will increase ASN motivation towards the organization and provide maximum work results. This research concludes that partial and simultaneous competency and compensation have a positive and significant influence on the motivation and performance of ASN at the Ministry of Religion, Muaro Jambi Regency. Likewise, motivation has a positive and significant influence on the performance of the ASN Ministry of Religion, Muaro Jambi Regency.